A Study of Interest in Astronomy Among University Students in Malaysia - Nur Farha Shaafi; M.M.M. Yusof; E. Ellianawati; S.N.A. Aziz (Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang, 2023)
The misconception related to astronomy is fretfully rising in society. This study aims to investigate, (i) level of misconception towards astronomy among university students, (ii) significant difference in students’ interest towards astronomy between male and female, (iii) significant difference between science and non-science students’ level of knowledge in astronomy, (iv) significant relationship between students’ faculties and misconception in astronomy, and (v) significant relationship between the educational background of the respondents' parents and their misconceptions towards astronomy. A qualitative approach was implemented using a set of questionnaires for data collection. The respondents were undergraduate students of with different courses and backgrounds from four different faculties: Faculty of Education, Faculty of Pharmacy, Faculty of Art and Design, and Faculty of Business Management. The data were analyzed using Statistical Package for the Social Science (SPSS). Findings showed that there is a significant difference in students’ interest towards astronomy between male and female students, there is a significant different between level of knowledge in astronomy and students’ major course, there is significant difference between students’ faculties and misconception in astronomy, and there is no significant relationship between the educational background of the respondents’ parents and their misconception in astronomy. This study benefits society by clarifying phenomena, distinguishing myth from reality. It aids Science teachers in addressing astronomy misconceptions and helps educators curb their spread.